2011
DOI: 10.1007/978-3-642-23765-2_18
|View full text |Cite
|
Sign up to set email alerts
|

Online Games and Family Ties: Influences of Social Networking Game on Family Relationship

Abstract: Abstract. How do online games impact intergenerational family relationships?To answer this question, we investigated QQ Farm, the most popular online game available on a popular Chinese social networking site. We conducted observations and semi-structured interviews with sixteen pairs of Chinese parents and their adult children. Of the sixteen pairs, seven lived locally; nine pairs lived remotely. The findings of this study suggest that online games provide common conversational topics among local family membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Others have noted that while there is minimal capacity in most social games for in-game social communication -apart from acts of exchange, gifting etc. -that the game itself and the ways in which it is embedded within a SNS is important even if only as providing a means of common reference point for conversations (Wen et al 2011). These observations accord with some of the written comments noted in the survey:…”
Section: Passing Time or Building?supporting
confidence: 74%
See 2 more Smart Citations
“…Others have noted that while there is minimal capacity in most social games for in-game social communication -apart from acts of exchange, gifting etc. -that the game itself and the ways in which it is embedded within a SNS is important even if only as providing a means of common reference point for conversations (Wen et al 2011). These observations accord with some of the written comments noted in the survey:…”
Section: Passing Time or Building?supporting
confidence: 74%
“…However, it is notable that none of the male players noted relieving stress as one of the most enjoyable activities (again possibly pointing to different gender stress relief practices). The use of social games as a way of managing the stress of the everyday is noted also in the open-ended comments (comments relating to stress management were only offered by female respondents): Considerable research has been devoted to investigating the sociality of social games (Wen et al 2011;Wohn et al 2011;Boudreau and Consalvo 2014;Rossi 2009). Critics have claimed the games are not social -the games position player's friends as purely resources, and the possibilities for in game communication are extremely limited raising questions about the types of sociality enacted (Bogost 2010;Rossi 2009;Consalvo 2011).…”
Section: Passing Time or Building?mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the ways in which grandparents and grandchildren manage these differences is in incorporating roles into play" (Davis et al, 2012, p. 28) (Aarsand, 2007;Boudreau & Consalvo, 2014;Chambers, 2012;Chen, et al, , 2013Chua, et al, 2013;Derboven, et al, 2012;Eklund, 2014;Follmer, et al, 2010;Khoo, 2011;Khoo, Merritt, & Cheok, 2010;Khoo et al, 2008;Khoo, Merritt, Cheok, Lian, & Yeo, 2007;Kow et al, 2012;Siyahhan et al, 2010;Voida & Greenberg, 2009;Wen, et al, 2011) -Use a player-centred approach: Involve both generations in the design process of games -Attend to the player's context Blast from the past Age invaders -Blur intergenerational gaps -Foster sense of togetherness (Chambers, 2012;Eklund, 2014;Follmer, et al, 2010;Khoo & Cheok, 2009;Khoo, et al, 2010;Loos, 2014;Nagai, et...…”
Section: Examples Of Intergenerational Digital Games and The Ways In mentioning
confidence: 97%
“…One study has examined how families in China play SNG together and found that parents and adult children who played the popular game QQ Farm used the game to provide common conversational topics among family members and to enhance awareness of remote family members' real-life activities (Wen, Kow, & Chen, 2011). Yet we know little about how families elsewhere play and make meaning from SNG.…”
Section: Information Communication and Societymentioning
confidence: 99%